Selection of Treatment Process for Textile Dye Wastewater Based on Their Bio-chemical Characteristics - Tagar, S; Zakira, U; Ahmed, F (Journal of Environmental Science and Natural Resources, 2015)
In Bangladesh most of the industries follow chemical treatment process for wastewater treatment without any effluent quality assessment. The aim of this study was to select an effective treatment process for effluent based on its bio-chemical characteristics. Wastewater samples from Textile Industries were collected in 9 batches over a period of 2 months (from17th November, 2011 to 28th April, 2012). Approximately 40liters composite samples were collected of several dying batches from inlet of the equalization tank. Sludge was collected from outlet point of settling tank. The physical, chemical and bio-chemical quality of untreated wastewater were assessed by analyses of some particular parameters in the laboratory and compared with ECR standard. Average concentration of EC (mS/cm), pH, COD (mg/L), BOD (mg/L) and BOD loading (kg/m3.d) were respectively 3.71, 9.24, 1472, 1024, and 0.205 respectively. For lower BOD loading, the treatment performance was found better..COD decreased rapidly during the first 8 hours of aeration and after 16 hours of aeration it became uniform. During the first 8 hr COD removal was more than 50% of the initial COD loading. The standard value of COD (200mg/l) was obtained within 12 to 16 hours of aeration for the initial BOD loading less than or equal 0.15 kg/m3.day and 24 hours of aeration for initial BOD loading 0.16 to 0.26 kg/m3.day and more than 24 hour for initial BOD loading greater than 0.26 kg/m3.day. The study revealed that volumetric loading is an important parameter for wastewater which to a great extent sets applicability limit of treatment process. From this laboratory model study, treatment process options have been recommended for industrial effluent having different bio-chemical characteristics. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22060 J. Environ. Sci. & Natural Resources, 6(1): 163-166 2013